Vibration Characteristics of Long-span Reinforced Concrete Hollow Flat Slabs: A Case Study - Li Zhou; Yong Huang; Bo Chen (Journal of Civil Engineering, 2026)
To investigate the vibration characteristics of the long-span reinforced concrete hollow flat slab, an actual engineering case was studied to examine the influence of parameters such as slab thickness and supporting beam cross-sectional dimensions on the dynamic properties of the floor. The dynamic response under human-induced loading was also analyzed. The study found that the thickness of floor slabs in the long-span zone significantly affects their fundamental frequency. As the total slab thickness varies from 450 mm to 850 mm, the fundamental frequency ranges from 5.043 Hz to 7.847 Hz, representing a 55.6% increase from the minimum value to the maximum. In contrast, the slab thickness in non-longspan zones and the cross-sectional dimensions of the supporting beams have a relatively small influence on the fundamental frequency. Both the magnitude and duration of the single-step gravity load influence the peak acceleration and vertical displacement of the floor. When the applied gravity load increases from 0.4 kN to 0.8 kN, the peak acceleration and maximum vertical displacement increase by 100.8% and 100.2%, respectively. When the load duration increases from 0.4 s to 0.8 s, the peak acceleration and maximum vertical displacement decrease by 51.1% and 22.7%, respectively. In contrast, the walking route has minimal effect on the dynamic response at the center of the slab